Pengaruh Return on Assets (ROA), Leverage dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan Perbankan yang Listing di BEI Periode Tahun 2012-2015 - Rini Handayani (Jurnal Akuntansi, 2018)
Taxes are compulsory contributions  from the subject of tax and designated to the State. The Company as one of the tax subjects who contributed the most in State tax revenues. Tax for companies is a burden that can reduce corporate profits while taxes for the State is income that will be used to fund the administration of the government. This difference of interest causes the company to manage the tax burden, both legally and illegally. Tax Avoidance is one way companies manage their tax expenses legally. This study aims to determine the influence of indicators of financial statements on Tax Avoidance. Return on Assets (ROA), Leverage and Company Size are used as indicators in the financial statements that may affect Tax Avoidance by the company. This research uses Causal Explanatory research type with sample selection in this research using purposive sampling method and hypothesis test using multiple regression test. The samples used in this research are banking companies go public listing on the BEI the period 2012-2015 totaling 69 companies. The result of this research shows that there is partially influence on Return on Assets (ROA) and Company Size to Tax Avoidance, while Leverage has no partial effect on Tax Avoidance. But simultaneously there is influence of Return on Assets (ROA), Leverage and Company Size to Tax Avoidance. Keywords:Tax Avoidance, Return on Assets, Leverage, Company Size